The Role of International Humanitarian Law in the Conflict with the West Papua Liberation Army - Muhammad Uchida Sudirman (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2025)
This research examines the application of International Humanitarian Law (IHL) in the conflict between the Indonesian National Armed Forces (Tentara Nasional Indonesia, or